Adsorption Batch Studies on the Removal of Pb(II) Using Maize Tassel Based Activated Carbon - Mambo Moyo; Linda Chikazaza; Benias Chomunorwa Nyamunda; Upenyu Guyo (Journal of Chemistry)
The demand for clean water is on the increase as rapid industrialization is still contributing to pollution. Nowadays, as water is the basic need for mankind, efforts have gathered momentum to decontaminate it in order to address the acute shortage of clean and pure water. Maize tassel was used as the precursor for making activated carbon for the adsorption of Pb(II) ions. The product obtained was characterized and utilized for the removal of Pb(II) from aqueous solutions over a wide range of initial metal ion concentration (10–50 mg/L), contact time (5–300 min), adsorbent dose (0.1–2.5 g), and pH (2–12). The optimum set of conditions for biosorption of Pb(II) ion were found to be initial concentration 10 mg/L, dosage 1.2 g, and pH 5.4. The adsorption data conformed to both the Langmuir and the Freundlich isotherms but fitted best into the Langmuir model. The R2 for Langmuir equation was 0.9997 and that for Freundlich was 0.9515. The Langmuir monolayer adsorption capacity of the activated carbon was calculated to be 37.31 mg/g. The results indicate that activated carbon might be used to effectively adsorb Pb(II) ions from wastewater treatment plants.